The Other Half of the Picture: Antecedents of Spouse Cross-Cultural Adjustment - Black, J. Stewart; Gregersen, Hal B. (Journal of International Business Studies, 1991)
Scholars have argued that the adjustment of the expatriate's spouse is an important factor in the success or failure of expatriates in overseas assignments; however, they have not empirically examined which factors are related to spouse adjustment. This study is the first to systematically examine the antecedents of spouse cross-cultural adjustment to interacting with host country nationals and to coping with the general, foreign environment. The results indicate that firms seeking the spouse's opinion about the international assignment, the spouse's self-initiated predeparture training, and social support from family and host country nationals during the overseas assignment have a positive relationship with spouse interaction adjustment. Additionally, firms' seeking the spouse's opinion about the international assignment and standard of living have a positive relationship with spouse general adjustment, while firm-provided training and culture novelty have negative relationships with spouse general adjustment. Several important research and practical implications are explored.